Analysis and design of a bidirectional cycloconverter-type high frequency link inverter with rural commutated phase angle control - Salam, Zail (Korean Institute of Power Electronics, 2011)
In this paper a cycloconverter-type high frequency transformer link inverter with a reduced switch count is analyzed and designed. The proposed topology consists of an H-bridge inverter at the transformer`s primary side and a cycloconverter with three bidirectional switches at the secondary. All of the switches of the cycloconverter operate in non-resonant zero voltage and zero current switching modes. To overcome a high voltage surge problem resulting from the transformer leakage inductance, phase angle control based on natural commutation is employed. The effectiveness of the proposed inverter is verified by constructing s 750W prototype. Experimentally, the inverter is able to supply a near sinusoidal output voltage with a total harmonic distortion of less than 1%. For comparison, a PSpice simulation of the inverter is also carried out. It was found that the experimental results are in very close agreement with the simulation.